Perbandingan Biaya Bunga dengan Pajak Penghasilan dalam Perencanaan Laba dan Perspektif Islam - Muhammad Rusdin; Muhammad Tafsir; Farida Aprianti; Nurlaely Razak (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to compare the effect of interest costs and income tax on sales to achieve the planned profit in the cost-volume-profit analysis. To compare the treatment of interest costs with income taxes in the profit and loss statement. To compare interest costs with income tax regarding halal or haram laws from an Islamic perspective. This research is library research using analytical methods: comparison, qualitative descriptive and quantitative descriptive. The research results show that interest costs and income taxes have the same effect on the need for higher sales to achieve the planned profit in the cost-volume-profit analysis. In the income statement, interest costs are taken into account when making a profit or loss; while income tax is taken into account only when profits are made. From an Islamic perspective, interest costs are haram; Meanwhile, according to the income tax law, some think it is halal and others think it is syubhat and some even think it is haram.